HUBUNGAN FAKTOR LINGKUNGAN DENGAN REHABILITASI TANAMAN KAKAO DI DESA NELOMBU KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR - Rahim, Difa Cahyani; Rosmawaty, Rosmawaty; Arif, La Ode Kasno (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the correlation between environmental factors and the rehabilitation of cocoa plantations in Nelombu Village, Mowewe District, East Kolaka Regency. The study population consists of 26 active cocoa farmers residing in Nelombu Village. The research sample was determined using the census method. The data presented herein was collected through the implementation of in-person interviews, which incorporated the use of a structured questionnaire. The research variables of interest were cocoa rehabilitation and environmental factors. The collected data was then analyzed using quantitative descriptive statistical methods and Spearman's rank correlation test. The findings of the study suggest that the robust correlation between environmental factors and cocoa plant rehabilitation can be attributed to intricate interactions among culture, society, and the individual impact of farmers. The mutually reinforcing relationship between these three factors is evident in the manner in which farmers manage their cocoa farms. This management is evident in the cultivation techniques employed, as well as in the decision-making processes related to variety selection, fertilizer use, pest control, and marketing. Consequently, the efficacy of management is contingent upon a harmonious equilibrium between conventional knowledge, social support systems, and access to superior information and resources. This underscores the significance of environmental factors in the context of cocoa farm management.